The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1682/jrrd.2010.12.0229
|View full text |Cite
|
Sign up to set email alerts
|

Preventive services in veterans in relation to disability

Abstract: Abstract-Veterans with disabilities are at an increased risk of secondary impairments and may have difficulty accessing preventive services; accessibility may differ between Veterans who do and do not receive care at Department of Veterans Affairs (VA) facilities. We used data from the 2003 and 2004 Behavioral Risk Factor Surveillance System surveys to evaluate associations between disability and receipt of preventive services in Veterans. Veterans with a disability were more likely to have received influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Although the current study did not investigate the reasons for such disparities, previous studies have suggested several factors as barriers to breast cancer screening related to disability: 1) system factors (eg, inaccessible facilities or equipment, transportation problems, insurance coverage or economic issues); 2) provider factors (eg, poor knowledge of disability, negative stereotyping and social misconceptions, and failure to recommend preventive services); and 3) patient factors (eg, disability‐specific barriers [eg, communication], competing health issues, lack of awareness or knowledge, misperceptions regarding screening, and lack of a usual source of care).…”
Section: Discussionmentioning
confidence: 97%
“…Although the current study did not investigate the reasons for such disparities, previous studies have suggested several factors as barriers to breast cancer screening related to disability: 1) system factors (eg, inaccessible facilities or equipment, transportation problems, insurance coverage or economic issues); 2) provider factors (eg, poor knowledge of disability, negative stereotyping and social misconceptions, and failure to recommend preventive services); and 3) patient factors (eg, disability‐specific barriers [eg, communication], competing health issues, lack of awareness or knowledge, misperceptions regarding screening, and lack of a usual source of care).…”
Section: Discussionmentioning
confidence: 97%
“…6 Those studies that have compared colorectal screening for disabled and nondisabled populations have sometimes produced somewhat surprising findings. 7–10 Some studies have found roughly equivalent colorectal cancer screening rates across persons with and without disability, 8,9 while others have identified significant differences but sometimes for only subgroups of persons with disability. 11 Occasionally these differences involve persons with disability having lower colorectal cancer screening rates than nondisabled persons.…”
mentioning
confidence: 99%
“…11 But in other studies, individuals with disability have higher colorectal cancer screening rates than nondisabled persons. 7,8,10 …”
mentioning
confidence: 99%
“…2730 In addition, VA stands out as an early adopter of women’s clinics for primary-care delivery 5,8,31 for one of the fastest growing segments of VA users—women Veterans. 32,33 Previous work on quality measures in VA has focused on the comparison of general screening measures between male and female Veterans in outpatient care such as immunizations, blood pressure, and diabetes screening, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on obesity is mixed showing obese body mass classifications as having a negative effect on receipt of cervical and breast cancer screening in non-Veterans 5 and conversely associated with increased screening or no difference in Veteran women. 68 Separately, mental health diagnoses generally show an effect of lower rates of cervical and breast screening overall, 9,10 but there is a small amount of literature indicating that some patients with mental illness have no difference in screening once they are at a site of usual care. 9 More striking is that there may be a more complex experience for mental health Veteran patients studied by Weitlauf and colleagues 11 whereby those who are low users of primary care often obtain screening, and conversely those who are high users often do not.…”
mentioning
confidence: 99%